Refining to Enhance Quality and Improve Specific Surface Area of Di Linh Bentonite for Adsorption Application - Nguyen, Thi Thuy; Vu, Minh Duc (JST: Engineering And Technology For Sustainable Development, 2022)
Bentonite derived from Di Linh, Lam Dong has a low SiO2/Al2O3 ratio (1.29), so the montmorillonite content in the bentonite is quite low. The mineral and chemical compositions show that this bentonite is of low quality and contains many impurities. A series of technological conditions were considered to provide the appropriate process and conditions for refining to enhance the quality and improve the specific surface area of Di Linh bentonite. Specifically, the bentonite (2 wt.%) was soaked for 24 hours in water before stirring for 8 hours at 1000 rpm. After drying, the refined bentonite was annealed for 2 hours at 500°C in a furnace. The final product obtained with the basal spacing of 17.38 Å and the specific surface area of 72.97 m² g⁻¹ was used to adsorb Pb²⁺ and active dyes. Thanks to the increase in the layer spacing and the specific surface area, both the adsorption capacity and the adsorption efficiency of Ben2-24-8-2 increased by 2.8 times compared to raw bentonite. While the dye adsorption took place slowly, the adsorption of Pb²⁺ ions was very fast and reached equilibrium after only about 0.5 hours. The Pb²⁺ ion adsorption capacity was 61.72 mg/g. The adsorption efficiency was 95.24% when using the Ben2-24-8-2 content of 2 g/L.